Disparities in accessing specialty behavioral health services during the COVID-19 pandemic and why we need pediatric integrated primary care - Chakawa, Ayanda; Crawford, Trista Perez; Belzer, Leslee Throckmorton; Yeh, Hung-Wen (Frontiers in Psychiatry, 2024)
Objective: Youth unmet behavioral health needs are at public health crisis status and have worsened since the onset of the coronavirus disease 2019 pandemic (Covid-19). Integrating behavioral health services into pediatric primary care has shown efficacy in addressing youth behavioral health needs. However, there is limited guidance on facilitating equitable access to care in this setting, including in triaging access to co-located services (i.e., onsite outpatient behavioral health services with only the behavioral health provider) or to specialty behavioral health services in other clinics within larger health systems.: A retrospective, comparative study was conducted to examine variability in access to co-located and specialty behavioral health (SBH) services for a pre-Covid-19 cohort (April 2019 to March 2020; n = 367) and a mid-Covid-19 cohort (April 2020 to March 2021; n = 328), while accounting for integrated primary care consultation services. The sample included children 1-18years old served through a large, inner-city primary care clinic. Logistic regression models were used to examine the association between scheduled and attended co-located and SBH visits, pre- and mid-Covid-19 effects, and sociodemographic factors of race and ethnicity, language, health insurance (SES proxy), age, and sex. The majority of youth were not directly scheduled for a co-located or SBH visit but the majority of those scheduled attended their visit(s). The odds of not being directly scheduled for a co-located or SBH visit were greater for the mid-Covid-19 cohort, Black youth, and older youth. Accounting for integrated primary care consultation visits addressed these disparities, with the exception of persisting significant differences in scheduled and attended co-location and SBH visits for Black youth even while accounting for IPC consultation. Implications: Findings from the current study highlight the effective role of integrated primary care consultation services as facilitating access to initial behavioral health services, especially given that referrals to integrated primary care co-located and SBH services within the larger health system often involve barriers to care such as longer wait-times and increased lack of referral follow through. Ongoing research and equitable program development are needed to further this work.